Characters and Space in the novel “Twilight of the Eastern Gods” by Ismail Kadare - Veron Dobroshi (Eon, 2023)
Space and description are important elements in, the literary work, which are closely related to the literary characters and their actions within the events. In the novel "Twilight of the eastern Gods" by Ismail Kadare, several interesting points of space and description are encountered. Many characters appear in this novel, which are also real names because they are directly related to the personal experience of the author and a period of his life. The study will highlight the characteristics of these characters and their relationship with the narrator of this novel and their function within the narrative. The characters are located within a space, therefore they are closely connected because it is the space where they act. The spaces in this novel are both external and internal. The study also includes another dimension, that of the translation of Kadare's work in Romania, as well as the cultural-literary ties between Albania and Romania.